2017
DOI: 10.4049/jimmunol.1601493
|View full text |Cite
|
Sign up to set email alerts
|

PACT Facilitates RNA-Induced Activation of MDA5 by Promoting MDA5 Oligomerization

Abstract: MDA5 is a RIG-I-like cytoplasmic sensor of dsRNA and certain RNA viruses, such as encephalomyocarditis virus, for the initiation of the IFN signaling cascade in the innate antiviral response. The affinity of MDA5 toward dsRNA is low, and its activity becomes optimal in the presence of unknown cellular coactivators. In this article, we report an essential coactivator function of dsRNA-binding protein PACT in mediating the MDA5-dependent type I IFN response. Virus-induced and polyinosinic-polycytidylic acid-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 48 publications
3
44
0
Order By: Relevance
“…PACT binds to dsRNA and recruit it to MDA5 or RIG-I. The authors claimed that ORF4a interrupt dsRNA-PACT interaction with the RLR's (Kok et al, 2011;Ho et al, 2016;Lui et al, 2017). Furthermore, when a recombinant MERS-CoV with ORF4a deletion infects cells, IFN induction was only marginally reduced (Comar et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…PACT binds to dsRNA and recruit it to MDA5 or RIG-I. The authors claimed that ORF4a interrupt dsRNA-PACT interaction with the RLR's (Kok et al, 2011;Ho et al, 2016;Lui et al, 2017). Furthermore, when a recombinant MERS-CoV with ORF4a deletion infects cells, IFN induction was only marginally reduced (Comar et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Despite having a helicase domain (including Hel2i) closely related to that of Dicer, PACT was proposed to bind RIG-I CTD, not Hel2i, and to stimulate the ATPase activity of RIG-I (190). However, in an apparent contradiction to these findings, more recent studies have shown that PACT is specifically involved in MDA5-mediated antiviral signaling, not RIG-I-mediated signaling (196,197). It was also proposed that PACT interacts with LGP2 in a dsRNA-dependent manner and that this interaction is required for PACT-mediated MDA5 stimulation (197).…”
Section: Author Manuscriptmentioning
confidence: 97%
“…Expression plasmid for FLAG-RIG-I was provided by Dr. Takashi Fujita (Kyoto University, Kyoto, Japan) (5). Expression plasmids for FLAG-PACT, Myc-PACT, and FLAG-PACT-DM have been previously described (6,11,27). PACT-DM is an RNA binding-defective mutant of PACT in which both RNA-binding domains are disrupted (27).…”
Section: Plasmidsmentioning
confidence: 99%
“…Expression plasmids for FLAG-PACT, Myc-PACT, and FLAG-PACT-DM have been previously described (6,11,27). PACT-DM is an RNA binding-defective mutant of PACT in which both RNA-binding domains are disrupted (27). V5-PACT expression plasmid was based on the pcDNA3.1/V5-his vector.…”
Section: Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation